On the sustainability of the economic model of the United States of America - Luyo Kuong, Jaime (2012)
A brief review is made of the main indicators of the distribution of wealth, employment, wages and inequality in the United States of America (USA) in the last decade, and the economic policy measures that have affected them and the role played by corporations and the powers of the State; then the opinions and reflections of experts, academics and heads of institutions linked to the American economy are presented; which allows us to draw some conclusions about the level of satisfaction of the Americans themselves with the economic model in force for nearly three decades.